Social Media Education for Students as an Effort to Build Digital Awareness - Muhammad Akhyar Aji Saputra; Rita Anisaturrizqi; Aiman Febriyanto; Alex Zidan Fadlullah; Ubaidillah Yoga Yazidi (PT. Riset Mandiri Nusantara, 2025)
The rapid advancement of digital technology has substantially affected the behavior and social interactions of elementary school students, particularly through the increasing intensity of social media use. This situation presents a dual challenge: it enables the improvement of digital literacy while simultaneously exposing children to the risks of digital addiction, exposure to inappropriate content, and cyberbullying. In response to these emerging challenges, a community service program was conducted by KKN MWC NU in Semboro Village, implemented at SDN 04 Semboro on August 15, 2025. The primary objective of this activity was to cultivate early awareness and understanding of ethical and responsible social media use among elementary school students. The methods employed included structured presentations on the impacts of social media, interactive discussions to evaluate comprehension, and educational games to foster engagement in the learning process. The results indicated that approximately 80% of fifth- and sixth-grade students possessed personal digital devices and actively accessed social media, yet lacked sufficient awareness of digital ethics. After the intervention, students demonstrated heightened enthusiasm, improved understanding of ethical online behavior, and increased awareness regarding responsible screen time management. The evaluation outcomes confirmed the effectiveness of the program in enhancing digital literacy and promoting wise, healthy, and productive social media practices among children. These findings highlight the importance of early digital education as a preventive strategy against the negative impacts of unregulated social media use